Kandungan Flavonoid dan Fenol Es Krim Buah Naga berbasis Tepung Daun Kelor untuk Remaja Putri - Yustika, Adelia; Junita, Dera Elva; Wati, Desti Ambar (Program Studi Gizi, Universitas Bumigora, 2025)
Adolescent anemia is characterized by iron deficiency associated with menstruation and unbalanced nutrient intake. Red dragon fruit and moringa leaf flour are rich in iron, flavonoids, and phenolic compounds, which possess antioxidant properties and may help prevent anemia. Both ingredients can be developed into snack products such as ice cream, which is popular among adolescents. The objective of this study was to analyze the total flavonoid and total phenolic contents in red dragon fruit ice cream with the addition of moringa leaf flour. This research employed a Completely Randomized Design (CRD) with five formulations and two replications. Chemical analysis and The ice cream was prepared at the Laboratory of Aisyah University, Pringsewu, in January 2025. Data were analyzed using One-Way ANOVA followed by Duncan’s multiple range test. The results showed significant differences (p < 0.05) among the formulations. The highest total flavonoid content was observed in formulation F4 (10%) with 0.53 mg quercetin equivalent per gram (p = 0.001). The highest total phenolic content was found in formulation F0 (0%) with 5.48 mg gallic acid equivalent per gram (p = 0.002). In conclusion, the addition of up to 10% moringa leaf flour in red dragon fruit ice cream increased the total flavonoid content but decreased the total phenolic content. Therefore, this product has potential as a functional food rich in antioxidant compounds that may benefit adolescent girls.